PENDEKATAN 5M (MAN, MACHINE, MATERIAL, METHOD, MONEY) PADA PROSES PRODUKSI PAKAIAN KONVEKSI SANDICH DALAM MENGHADAPI BULLWHIP EFFECT - Khoirun Nisa; Abi Hanif Dzulquarnain (MANAJEMEN DEWANTARA, 2026)
This study aims to analyze the implementation of the 5M approach (Man, Machine, Material, Method, and Money) in the production process at Sandich Convection and its role in addressing the Bullwhip Effect, a phenomenon characterized by increasing fluctuations in demand from consumers to producers, which results in production imbalances, delays, and cost inefficiencies. This study employed a qualitative descriptive approach. Data collection techniques included interviews, observations, and documentation with informants consisting of the owner and employees of Sandich Convection. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that in the Man element, there are challenges in workforce management when demand increases, leading to overtime and delays. In the Machine element, the machines are in good condition but require routine maintenance. In the Material element, raw material availability is not well planned. In the Method element, the lack of SOPs makes the process less structured. In the Money element, limited capital is a barrier. Improvements include task allocation, communication, machine maintenance, raw material planning, systematic work method development, and more effective financial management.